Metagenomics and CAZymes in Rumen: A review - Kala, Anju; Kamra, Devki Nandan; Chaudhary, Lal Chandra; Agarwal, Neeta (Indian Journal of Animal Nutrition, 2019)
Rumen is wonderful machinery that converts lignocellulsic biomass to high quality food, by virtue of the diverse microbiota it harbours. The composition of rumen ecosystem is shaped up by various factors including diet, individuality, age, geographic region, postfeeding time etc. Earlier culture based techeniques could study rumen microbes partially for the cultivable microbes. But, now it is known that about 90% of rumen microbes are unculturable, and the knowledge that we have till now seems very meager. With advent of new technologies as next generation sequencing, which studies the whole ruminal ecosystem at one time, has contributed tremendously to our existing knowledge. Approaches like metagenomics, metatranscriptomics have made it possible to study the structure and function of rumen microbes in their natural environment. The study of CAZymes has revealed that there is an array of hydrolytic enzymes in rumen that performs the deconstruction of fibrous feed material. Also, these enzymes are not only contributed by well known microbes’ viz. Fibrobacter and Ruminococcus, but by a very diverse microbiota including Roseburia, Porphryomonas, Balutia etc. So, metagenomics has added to our knowledge in many spheres of rumen microbiology, its composition and interactions in rumen. But the problem in this field is that a robust database is not available to compare the data obtained. Much work is required in field of analysis of metagenomic database establishment.